Acute Heart Failure Caused by Parvovirus B-19 Myocarditis Treated with Human Immunoglobulin - Luca Alberti; Marco Loffi; Gabriele Fragasso; Roberto Spoladore; Carlo Ballarotto; Alberto Margonato (Case Reports in Cardiology)
We describe the case of a 42-year-old woman developing cardiogenic shock with cardiac tamponade due to an acute myo-pericarditis caused by Parvovirus B19 (PVB19), successfully treated with intravenous (iv) immunoglobulin administration.